Insecticidal Activity of Crude Flower Stalk Extract of Forest Clove (Syzygium aromaticum L) Against Larvae of Asian Armyworm (Spodotera litura F) (Lepidoptera: Noctuidae) - Misda Alberto Senen; Johanna Audrey Leatemia; Betty Sahetapy (Fakultas Pertanian, Universitas Pattimura Ambon, Indonesia, 2025)
The intensive and prolonged use of synthetic insecticides in agriculture has resulted in multiple adverse effects, including pest resistance and resurgence, reduction of natural enemy populations, and risks to environmental and human health. Botanical insecticides offer a promising alternative for more sustainable pest control. This study evaluated the insecticidal activity of crude ethanolic extract from flower stalks of forest clove (Syzygium aromaticum) against the tropical armyworm, Spodoptera litura (Lepidoptera: Noctuidae). Laboratory bioassays were conducted to determine larval mortality and lethal concentration of 50% (LC₅₀) at 48 hours after treatment, while plastic house experiments assessed the extract’s efficacy on S. litura infesting mustard plants. Chemical composition of the extract was analyzed using gas chromatography–mass spectrometry (GC–MS). The extract contained four major classes of secondary metabolites—terpenoids, phenolics, flavonoids, and alkaloids—with flavonoids as the dominant constituent (21.48%). Laboratory bioassays yielded an LC₅₀ value of 1.5% (w/v). In plastic house trials, larval mortality reached 100% within 96 hours at 1.5% and 3% concentrations, and within 72 hours at 6%. These findings indicate that the crude extract of forest clove flower stalks possesses potent insecticidal activity and has strong potential for development as a botanical insecticide that may contribute to more environmentally compatible pest management strategies